The Role of Nurses in Enhancing Patient Safety: Strategies for Error Prevention (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Patient safety is a fundamental principle of healthcare delivery, and nurses, as the largest group of healthcare professionals, are at the forefront of its implementation. Medical errors remain a leading cause of morbidity and mortality globally, necessitating robust and proactive strategies to mitigate risk. This paper examines the critical and multifaceted role of nurses in enhancing patient safety and preventing errors. It explores the systemic, human, and environmental factors that contribute to errors and outlines evidence-based strategies nurses employ at the bedside, within units, and across healthcare systems. Key areas of focus include the adoption of a safety culture, effective communication techniques like SBAR, adherence to clinical protocols (e.g., medication administration, central line care), the use of technology and checklists, and the importance of patient education and empowerment. The paper concludes that empowering nurses through leadership support, continuous education, and a just culture is paramount to sustaining safety improvements and achieving the goal of zero preventable harm.